The effects of customer-centricity in hospitality. (April 2020) - Inversini, Alessandro; De Carlo, Manuela; Masiero, Lorenzo
Highlights: Hoteliers feel Customer Centricity could be improved in areas such as organization operations, organization process and key performance indicators. An effective implementation of advanced Customer Relationship Management tool could be considered as an enabler of custom centricity in the hospitality field. There is a positive correlations among software usage, customer centricity culture and online reputation in hospitality. Customer centric hospitality establishments show an increase of rating in users' reviews. Rating increase may have a positive impact on average daily rate, occupancy and revenue per room. Abstract: Hospitality is a field in which guests' specific needs and wants should always be given serious consideration by hoteliers. Putting the guest at the centre of all business efforts contributes to generating customer value and enhancing a firm's competitiveness. Being customer-centric is paramount for hospitality establishments to create and sustain superior customer value. However, there is scant evidence in hospitality marketing literature of a clear understanding of the customer-centricity concept or of the possible effects of its implementation. Using a mixed-methods multiple case study approach, this research studies two different properties that, to some extent, are already engaged in customer-centricity practices through the use of advanced Customer Relationship Manager software. Results clearly show an increase in customer ratings, leading to possible profit implications; a cultural shift within the organizations studied connected with the customer-centricity phenomenon has also been reported.